Mitigasi Abrasi Pantai Bita Beach Melalui Penanaman Pohon Waru - Agustinus F Paskalino Dadi; Hironimus Epe Nagu; Maria Moset; Romilius Aditia Rema; Antonius Juliant Padua; Rasyada Ibrahim Rasyid (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Bita Beach is a coastal area of the south coast in the Mautapaga District. This beach is located on the coast of the Sawu Sea, which is directly connected to the Indian Ocean. Therefore, this region often experiences the impact of extreme weather anomalies. The southern coastal region often experiences abrasion due to tidal waves. The presence of abrasion vulnerability is also due to the lack of vegetation in coastal areas. When the tide is high, the coastal area often experiences abrasion, and a slight wave can wash up on the houses of residents. Faced with these conditions, one solution is to implement abrasion mitigation activities. The mitigation activity determined is the planting of Waru Trees. Of course, this is not the result of the team's speculation but of its research into various mitigation best practices across different areas affected by abrasion. Waru trees have been proven to thrive in dry, hot coastal regions. Waru also has sturdy trunks and strong roots, so it can be relied on to control the speed of sea waves in the coastal areas (mitigating coastal abrasion). This abrasion mitigation activity is also part of the implementation of project-based MKWK to overcome environmental problems faced by the coastal community of Bita Beach. With the implementation of this activity, students have been involved in providing solutions to the problem of abrasion as well as forming the character of Pancasilais to provide the basic direction of education towards the realization of a young generation that is intellectual, noble, human, and has a sense of nationality based on Pancasila and UUD 1945.